Estudo por microscopia/espectroscopia de tunelamento e difração de raios x da correlação entre propriedades estruturais e eletrônicas de grafeno epitaxial sobre cobre - Thais Chagas Peixoto Silva (2016)
In this work we have used atomically-resolved scanning tunneling microscopy and spectroscopy to study the interplay between atomic and electronic structure of graphene formed on copper via chemical vapor deposition. In particular, we studied the interplay between strain modulation and electronic band modification induced by the substrate. Scanning tunneling microscopy directly revealed the epitaxial match between a single layer of graphene and the underlying copper substrate in different crystallographic orientations through the disclosure of different Moiré patterns. Using scanning tunneling spectroscopy we have directly measured the electronic density of states of graphene layers near the Fermi level, observing the appearance of a series of peaks in specific cases. These features were analyzed in terms of substrate-induced perturbations in the structural and electronic properties of graphene by means of atomistic models supported by density functional theory calculations. Finally, we have used grazing incidence diffraction to confirm our proposed structural model.